COMPUTATIONAL SYSTEM APPLIED TO MOBILE TECHNOLOGY FOR EVALUATION AND TREATMENT OF WOUNDS. - Batista da Cunha, João; Alves Dutra, Rosimar Aparecida; Magela Salomé, Geraldo; Masako Ferreira, Lydia (Journal of Nursing UFPE / Revista de Enfermagem UFPE, 2018)
Objective: to describe the development of a mobile application for evaluation and treatment of wounds. Method: methodological study. Literature search was carried out with the descriptors: wounds and injuries; dressings; cicatrization. The following steps were followed: planning of content; selection of application tools; configuration of environments, tools and educational resources; building the Internet environment for downloading and installing the application on mobile devices. Results: fifteen articles were selected through literature search. The application has an easy-to-use graphical interface. It stores the patient's sociodemographic characteristics, allows assessment of the wound and risk factors and recommends therapeutic procedures. Conclusion: the application developed may be very useful in clinical practice, helping to select nursing interventions for wound prevention and treatment, as well as in nursing education.